How to manage training : facilitating workplace learning for high performance - Nilson, Carolyn D. (American Management Association, 2007)
The knowledge, skills and guidance managers need to become true learning leaders. Now more than ever, a versatile, well-trained workforce is critical to an organization's success. Written for managers from a wide range of functional areas, this book gives any manager responsible for training the tools to help employees learn more, perform better, and work smarter. This comprehensive, up-to-date guide targets the roles necessary to manage training and learning in an organization: champion, builder, performance consultant, supporter, administrator, and keeper of the budget. Filled with expert in.